Educational robotics - kinematics - Tan, Chin Hoe. (2012)
The objective of this project is to simulate a virtual 3D model and design an easy Graphical User Interface program for the students for their understanding of basic concept in robotics called kinematics. It also serves as a teaching aid to the students’ interest.